2021
DOI: 10.3390/hydrology8040164
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatological Patterns and Limnological Characteristics of Unique Wetland Systems on the Argentine High Andean Plateau

Abstract: High-elevation wetlands in South America are not well described despite their high sensitivity to human impact and unique biodiversity. We describe the hydroclimatological and limnological characteristics of 21 wetlands on the High Andean Plateau of Argentina, synthesizing information gathered over ten years (2010–2020). We collected physical-chemical, phytoplankton, and zooplankton data and counted flamingos in each wetland. We also conducted an extensive analysis of climatic patterns and hydrological respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 107 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…Recent work by Moran et al, [14] establishes that modern water accounts for a small portion of water budgets but is critical to sustaining surface water bodies and wetlands, as a result, these arid systems are uniquely sensitive to climate (drought) and anthropogenic perturbations on short time scales. Much of the work to date has been focused on the western edge of the Dry Andes, while other work has explored these issues in basins further east [52][53][54] but a mechanistic framework to explain hydrological and hydrogeochemical observations region-wide has not been established. Substantial gaps remain in our understanding of the time scales and spatial definition of primary interconnections that constitute water cycles in these environments, specifically the controls on groundwater, surface water, and modern climate interactions [55].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Moran et al, [14] establishes that modern water accounts for a small portion of water budgets but is critical to sustaining surface water bodies and wetlands, as a result, these arid systems are uniquely sensitive to climate (drought) and anthropogenic perturbations on short time scales. Much of the work to date has been focused on the western edge of the Dry Andes, while other work has explored these issues in basins further east [52][53][54] but a mechanistic framework to explain hydrological and hydrogeochemical observations region-wide has not been established. Substantial gaps remain in our understanding of the time scales and spatial definition of primary interconnections that constitute water cycles in these environments, specifically the controls on groundwater, surface water, and modern climate interactions [55].…”
Section: Introductionmentioning
confidence: 99%
“…As global climate change becomes increasingly apparent, assessing impacts in SdA in the context of these changes will become even more important. Indeed, a recent study found that mean annual temperatures have already increased by >0.5°C over large parts of the dry Andes since the 1980s (Frau et al., 2021). The most recent projections of climate change in this region over the next several decades show that average temperatures will continue to increase (by 2–5°C by 2100), though it is important to note that due to the strong influence of the Pacific sea surface temperatures on the regional climate, natural modes of variability have caused hiatuses in this broader warming trend that may also occur in the future (Vuille et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This process also increases the concentration of lithium in the groundwater, which mining companies extract in order to meet the accelerating demands of the lithium‐ion battery market (Munk et al., 2016). Surface water in these environments is a focal point of ecosystem diversity for microbial organisms (Farias et al., 2017) and habitat for the Andean flamingo (Frau et al., 2021; Hurlbert & Keith, 1979; Marconi et al., 2022). Anthropogenic extraction has raised questions about the resilience of such ecosystem‐critical surface water in the context of multiple hydrologic perturbations (Babidge et al., 2019).…”
Section: Current Understanding Of and Recent Technological Advancemen...mentioning
confidence: 99%